The Implementation of Healthy Food Diet for High-Risk Pregnant Woman (Amaris) Class on The Level of Knowledge and Attitude of Pregnant Woman - Rina, Diyah Alva; Meliati, Linda (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
High-risk pregnant women is a period where pregnant women can experience a variety of risks that are influenced by various factors. If a pregnant woman has more knowledge about the high risk of pregnancy then it is likely that mothers will think of overcoming the problem of risk of pregnancy. High-risk pregnant class mothers with a Healthy Food Diet High Risk Pregnant Women (AMARIS). is one of the means to increase mothers' knowledge and attitudes about pregnancy care. The purpose of this study was to determine the effect of high-risk classes of pregnant women on the level of knowledge and attitudes of mothers about pregnancy care. This study used a pre-experimental research design with one group pretest-posttest, with a total sample of 30 people. The results of the study showed an increase in the average score of knowledge and attitudes after being given a class of resting pregnant women. The average knowledge score before resti pregnant women class was 71.77, while thereafter increased to 88.22. The average score before resting pregnant women for attitude was 72.66, while after that it increased to 77.83. There is an influence of AMARIS class on the level of knowledge and attitudes of high risk pregnant women with p value = 0,000. There is an influence of the Amaris class on the level of knowledge and attitudes of high-risk pregnant women.